Apologetika Imajinatif: Sebuah Proposal bagi Apologetika dalam Konteks Pascamodern: Imaginative Apologetics: A Proposal for Apologetics in Postmodern Context - Aruan, Abel Kristofel (Veritas : Jurnal Teologi dan Pelayanan, 2021)
For a long time, classical and evidential apologetics have been firmly established as a way of defending the Christian faith. However, postmodernism appears to criticize the use of absolute verification tools for faith claims. Nevertheless, James K.A. Smith and Alister McGrath see postmodernism as friend rather than foe, opportunity rather than challenge. Therefore, paying attention to important criticisms of the spirit of postmodernism will actually help the church to answer the demands of postmodernism itself. This article proposes an imaginative apologetics approach as a solution to answer this criticism. In contrast to classical/evidential apologetics, this apologetics tends to use imagination more than before in efforts to account for the Christian faith. When apologetics accepts dry accusations and seems to override existential aspects that actually dwell in humans, imaginative apologetics can be a proposed solution to avoid these accusations. Two implications emerge from this reasoning. First, in apologetic dialogues, an apologist must use more imaginative rhetorical tools. Second, the church must help listeners get an imaginative presentation of what it’s like to live as a Christian, by presenting them with stories of everyday Christian life. Thus, instead of the church using apologetics, the church is apologetics itself.